ANALISIS PERSEPSI MUZAKKI DALAM MEMBAYAR ZAKAT FITRAH DI LEMBAGA AMIL ZAKAT : STUDI ZAKAT FITRAH DI LAZ BAITUL MAAL HIDAYATULLAH KOTA JAMBI - Muammar, Muammar; Syahrizal, Ahmad; Ahmad, Syahril (Lembaga Pengembangan Kinerja Dosen, 2023)
Zakat fitrah is zakat by which a Muslim gives part of his wealth to people in need as a form of purifying his soul from evil during the fasting month, such as dirty words and useless deeds. The purpose of this study was to determine the perceptions of muzakki in paying zakat fitrah at LAZ BMH Jambi City and to find out the efforts of LAZ BMH Jambi City to increase muzakki's interest in paying zakat fitrah at LAZ BMH Jambi City. In order to present this issue in detail and comprehensively, the author uses qualitative research methods to collect the necessary information during the investigation period. Data collection for this study was carried out by observing, interviewing and documenting. The validity test used in this study is using a triangulation technique. Based on the results of this study, it shows that the muzakki's perception of paying zakat fitrah at LAZ BMH is quite good even though the muzakki's understanding of LAZ BMH in Jambi City is still very low. As well as the efforts of LAZ BMH Jambi City to increase muzakki's interest in paying zakat fitrah at LAZ BMH Jambi City, namely by outreach, collaboration, and improving service quality.